A Triphasic Metacognitive Formulation of Problem Drinking. (16th May 2012) - Spada, Marcantonio M.; Caselli, Gabriele; Wells, Adrian
<x xml:space="preserve">Abstract</x> In this paper, a triphasic metacognitive formulation of problem drinking and its implications for treatment are presented together with a summary of the evidence consistent with this approach. In the triphasic formulation during the pre‐alcohol use phase, alcohol‐related triggers, in the form of cravings, images, memories or thoughts, activate positive metacognitive beliefs about extended thinking, which lead to desire thinking, rumination and worry or their combination. The activation of the latter brings to an escalation of cravings and negative affect, strengthening negative metacognitive beliefs about the need to control thoughts and enhancing the likelihood of alcohol use. In the alcohol use phase, positive metacognitive beliefs about alcohol use and a reduction in metacognitive monitoring contribute to dysregulation in alcohol use. Over the course of time and as the drinking problem escalates in severity, negative metacognitive beliefs about the uncontrollability of alcohol use and alcohol‐related thoughts emerge, contributing to the perseveration of dysregulated alcohol use. In the post‐alcohol use phase following the activation of positive metacognitive beliefs about post‐event rumination, the affective, cognitive and physiological consequences of dysregulated alcohol use become the subject of rumination. This, in turn, leads to a paradoxical increase in negative affect and alcohol‐related thoughts, together with the strengthening of negative metacognitive beliefs about such thoughts. Intermittent attempts to suppress alcohol‐related thoughts increase the likelihood of returning to use alcohol as a means of achieving self‐regulation. Copyright © 2012 John Wiley & Sons, Ltd. Key Practitioner Message A metacognitive formulation of problem drinking that may aid assessment, conceptualization and treatment across the problem drinking spectrum.